(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2005)
New etching trace fossils produced by the attachment of balanid barnacles on fossil molluscs, mainly bivalves, from the Upper Miocene of Cacela (southern Portugal) and Lower Pliocene of Huelva (southwestern Spain) are described. These traces are named as Anellusichnus igen. n. due to the ring-like shape of the scars. Two ichnospecies are recognized: A. circularis n. isp., consisting in a circular scar defined by a discoloured area or by a circular to subcircular trench and A. undulatus n. isp. that has a sinuous perimeter reflecting the undulate pathway of the furrow and a flat shelf etched into the substrate. Within the outer furrow both can display a cluster of circular, oval or subpolygonal concentric lines. A. undulatus n. isp. shows several morphologies that correspond to different ontogenetic stages. SHORT NOTE